Simvastatin Downregulates the SARS-CoV-2-Induced Inflammatory Response and Impairs Viral Infection Through Disruption of Lipid Rafts - Teixeira, Lívia; Temerozo, Jairo R.; Pereira-Dutra, Filipe S.; Ferreira, André Costa; Mattos, Mayara; Gonçalves, Barbara Simonson; Sacramento, Carolina Q.; Palhinha, Lohanna; Cunha-Fernandes, Tamires; Dias, Suelen S. G.; Soares, Vinicius Cardoso; Barreto, Ester A.; et al. (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) is currently a worldwide emergency caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). In observational clinical studies, statins have been identified as beneficial to hospitalized patients with COVID-19. However, experimental evidence of underlying statins protection against SARS-CoV-2 remains elusive. Here we reported for the first time experimental evidence of protective effects of Simvastatin treatment both in vivo and in vivo. We found that treatment with simvastatin significantly reduced SARS-CoV-2-associated mortality and delayed weight loss induced by SARS-CoV-2 in the K18-hACE2-transgenic mice model. Simvastatin downregulated the production of key pro-inflammatory cytokines triggered by SARS-CoV-2 infection in human neutrophils, peripheral blood monocytes, and lung epithelial Calu-3 cells, showing its potential to modulate the inflammatory response both at the site of infection and systemically. Additionally, simvastatin affected the course of SARS-CoV-2 infection by inhibiting the virus entry through displacing ACE2 on cell membrane lipid rafts. In conclusion, our results show that simvastatin exhibits early protective effects on SARS-CoV-2 infection by inhibiting virus cell entry and inflammatory cytokine production, through mechanisms at least in part dependent on lipid rafts disruption.